Epigenetic Mechanisms in Heart Diseases - Mustafa Yildiz (Reviews in Cardiovascular Medicine)
Heart diseases (HDs) continue to be among the major diseases that adversely affect human health worldwide, with complex interactions between genetic, environmental, and biochemical factors contributing to their progression. These include coronary heart disease, hypertension, heart failure, vascular calcification, etc. Cardiovascular diseases have been extensively studied in the Framingham Heart Study since 1948, spanning three generations over the past 70 years, and are highly correlated with various factors, including biochemical, environmental, behavioral, and genetic factors. In recent years, epigenetic mechanisms have emerged as crucial regulators of cardiovascular pathology, influencing gene expression without altering the underlying DNA sequence. Moreover, early detection and diagnosis of heart diseases are crucial for improving treatment and prognosis. Recent studies on heart disease have found that the expression of potential candidate genes related to the disease is associated with epigenetic mechanisms. Indeed, abnormal methylation states have been detected in candidate genes that can serve as biomarkers to assess the progression of heart disease. Recent advances in next-generation sequencing techniques have contributed significantly to our understanding of heart diseases, including the role of DNA methylation, adenosine triphosphate (ATP)-dependent chromatin conformation and remodeling, post-translational modifications of histones and non-coding RNAs. Lastly, this review examines the latest discoveries in the epigenetic regulation of heart diseases, highlighting the roles of DNA methyltransferases (DNMTs), histone deacetylases (HDACs), sirtuins (SIRTs), and ten-eleven translocation proteins (TETs). Additionally, this review highlights preclinical therapeutic strategies targeting epigenetic modifiers, offering new avenues for precision medicine in cardiology. Understanding these epigenetic pathways is crucial for developing novel biomarkers and epigenetic-based therapies that aim to reverse maladaptive cardiac remodeling and enhance clinical outcomes.